Digitally-Induced Altered States of Consciousness and Playful HCI: Future Research Agenda of a Novel Perspective - Belousov Anatolii; Ojell-Järventausta Terho; Bujić Mila; Macey Joseph; Hamari Juho (United States, 2025)
Due to the increasing availability and efficiency of digital technologies humanity has reached a point where digitally altering consciousness might become ubiquitous, echoing in all areas of the functioning of society. In addition to the already familiar functions in terms of conveying information, enabling experiences, and extending our realities, there is an emerging field of digitally-induced altered states of consciousness (DIAL). Precursors of the societal impact of DIAL technologies include various examples from binaural beats to video games that provide invaluable insights into forthcoming DIAL technologies. Although individual changes in consciousness through digital means have been studied for decades, they have been limited to the reach of technology. We suggest the field DIAL denotes the class of all digital technologies exploited for inducing altered states of consciousness (ASC). It supports a focused and holistic approach to anticipating futures and astute actions. We highlight the need for a detailed and full-fledged examination by demonstrating existing and hypothetical examples of their impact on Political, Economic, Social, Technological, Environmental and Legal (PESTEL) contexts. Based on these reflections we outline a potential research agenda to elicit discussions within the interdisciplinary community.
CHI PLAY '23: The Annual Symposium on Computer-Human Interaction in Play